Asset-based approaches to promote health in place-based communities: when the context matters. (30th September 2020) - Cassetti, V; Powell, K; Barnes, A; Sanders, T
Abstract: Background: In recent years, asset-based approaches (ABAs) to promote health have increasingly been adopted as a strategy to reduce health inequalities between neighbourhoods. However, evidence of impact is still limited due to their complexity. This research aimed to explore what changes ABAs generate, studying two asset-based initiatives that train local lay people to become peer health promoters, implemented in two different settings (Spain and UK). Methods: A five months ethnography was conducted in each setting between March 2018 and March 2019. Data were collected through 127 hours of observations and interviews with 44 participants (learners, community workers and health professionals). Thematic analysis was performed to explore the impacts of the interventions and their interactions with local contexts. Results: Preliminary findings indicate that learners' self-confidence, knowledge and skills for addressing local health determinants increased in both settings. However, contextual factors played an important role in supporting or hindering wider impacts in the communities where the initiatives were implemented. Opportunities for working together across sectors and being supported by local institutions were key elements supporting learners to transfer the acquired confidence, skills and knowledge to other settings beyond the time and space of the initiatives. These learners reported volunteering more in their communities, developing new activities, or transferring skills in their workplace to change practice and attitudes. Conclusions: This study found that ABAs initiatives implemented in communities have the potential to support reduction of inequalities through increasing people's skills, knowledge and self-confidence. However, it is key to work intersectorally to create enabling environments where these acquired capacities can be mobilised, as the context can support or hinder wider changes to occur. Key messages: Asset-based interventions to promote health increase people knowledge, skills and self-confidence, but it is key to consider how contextual factors can favour or hinder the potential for wider impacts. Community structures and institutional support for joint working influence mobilisation of learners' acquired confidence, skills and knowledge beyond the formal spaces of asset-based interventions.